Biodiversity, phylogeny and biogeography of the family Sphaeriidae (Mollusca: Bivalvia) in Morocco - Rassam, Hanane; Justus Liebig University Giessen (My University, 2022)
The family Sphaeriidae Deshayes, 1855 is widely distributed across the globe, except for Antarctica, with a high species richness of up to 200 species. In Morocco, freshwater bivalves are receiving more and more attention in recent years and data on the families of this group are no longer a mystery for most of them. However, many uncertainties surround the current diversity and distribution of the family Sphaeriidae. This information, including taxonomy, phylogeography and conservation status, is essential for further studies to improve knowledge of this family in Morocco and represents the first step towards the development of a national conservation plan for all freshwater bivalves. In the present work, several investigations were carried out to evaluate the diversity and distribution of Sphaeriidae in the different basins of Morocco, covering different types of habitats (lakes, springs, rivers and small ponds) and microhabitats (mud, aquatic plants, etc). The identification of specimens and their morpho-ecological characteristics was based on morphological and morphometric analyses carefully processed to obtain maximum precision. Several studies have shown, however, the influence that environmental factors can have on the morphology of species, especially for species with a high morphological plasticity that can distort their identification. A case study was proposed for the species Pisidium casertanum, evaluating the intraspecific morphological variability according to the habitats of the species by the application of Fourier Elliptic Analysis, a geometric morphometric method analyzing the contour of the specimens. To complete the morpho-geometric analyses of the species and to confirm their identification, molecular analyses were carried out by integrating the sequences resulting from the amplification of four genes, mitochondrial (COI and 16S rRNA) and nuclear (H3 and 28S rRNA). These Moroccan sequences, complemented with other Pisidium sequences, were integrated to infer, for the first time, their phylogeographic history in a larger framework: the Western Palearctic. Shell morphology and morphometric analyses combined with molecular data revealed the existence of five species belonging to the genus Pisidium [P. casertanum (Poli, 1791), P. (cf.) personatum Malm, 1855, P. subtruncatum Malm, 1855, P. amnicum (O. F. Müller, 1774) and Pisidium sp.and one species belonging to the genus Musculium: M. lacustre (O. F. Müller, 1774). Sphaeriidae have been collected in all Moroccan basins, except for the Bouregreg and Sakia El Hamra-Oued Eddahab basins. The conservation status of Sphaeriidae in Morocco was evaluated for the first time and allowed updating the statuses previously assigned by the IUCN. Pisidium casertanum and P. (cf.) personatum are both classified as "Least Concern" while P. subtruncatum has been proposed as "Vulnerable", as the number of sites where these species are present is now more important. The status of "Regionally Extinct" is suggested for P. amnicum and M. lacustre as only empty shells have been found for both species. The molecular clock used for the phylogeographic analysis allowed determining the dates and processes of divergence that have shaped the present diversity and distribution of the genus Pisidium in the Western Palearctic. These results showed that the presence of the genus in the Western Palearctic is the consequence of a dispersal from a locality of Eurasian origin during the early Oligocene period. This dispersal would have taken place via two routes: a northern route after the closure of the Turgai Strait connecting Asia to Europe; and a southern route when the Paratethys Sea separated from the Tethys Ocean giving rise to the Anatolian-Balkan-Iranian land mass. The radiation of Pisidium species in the Western Palearctic was maximal during the late Miocene and continued until the Pliocene. These radiations are mostly related to speciation that resulted from isolations in glacial refuges at the Mediterranean peninsulas. However, no clear geographic pattern has been identified between Moroccan and other populations, which is probably due to the dispersive nature of members of the family Sphaeriidae that can be transported long distances by birds and fish. All the information received through this work constitute basic elements to improve the knowledge on this family and to invest them in future projects of work on their bio-ecology, conservation and implication in ecotoxicological studies.
Biodiversität, Phylogenie und Biogeographie der Familie Sphaeriidae (Mollusca: Bivalvia) in Marokko
Keywords: Systematics; Distribution; Phylogeography; bivalves; freshwater; Morocco; ddc:570